Ensaio n°13: uma fotocartografia metateatral na Amazônia - DANTAS, Márcia Danielle Cascaes (2021)
Undergraduate paper written in order to obtain the title of Theatre Teacher at the Universidade Federal do Estado do Pará - UFPA. Rehearsal nº 13: a metatheater photocartography in the Amazonian Area, is a poetic and reflective work about the different places that the photographer acts, literal and abstract. Is a reflection about the theatre photographer's invisibility, using Emidio Luisi's work. Is, too, a dialog with the present viewer, and the photographic viewer, the one that only had access to the scene through image, crossing the two experiences and adding them to the photographer's personal experience, using the concepts of coletivity presents in Wlad Lima's thesis.